ANALYSIS OF SUSTAINABILITY ECONOMIC PERFORMANCE ASPECTS IN THE CORPORATE SOCIAL RESPONSIBILITY OF BANK BJB SYARIAH - Kamaludin, Asep; Jubaedah, Dedah (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study compares and contrasts the concepts of CSR Pyramid Carrol andCSR Perspective Islam. There are significant philosophical and objective distinctions between the two ideas. In addition to maximizing profit and fostering public trust, CSR Pyramid Carrol is typically focused on addressing issues of poverty. On the other hand, CSR is associated with human social and individual responsibility from an Islamic perspective. Analysis of Bank BJB Syariah's sustainable economic performance provides an overview of the company's commitment to carrying out every activity by corporate social responsibility through the three CSR pillars: profit, people, and planet, and by the Carroll Pyramid CSR concept. This study used a qualitative approach, which is defined as research that aims to identify, assess, characterize, and explain the nature or specialization of social factors that a quantitative technique cannot adequately explain. Library research is the scientific approach employed, specifically research that uses information and data gathered from various sources in the literature. The study's findings anticipate an overview of the current concept compared to the tenets of the Islamic concept